The impact of Taiwan's implementation of a nationwide harm reduction program in 2006 on the use of various illicit drugs: trend analysis of first-time offenders from 2001 to 2017 - Wei J. Chen; Chi-Ya Chen; Shang-Chi Wu; Kevin Chien-Chang Wu; Susyan Jou; Yu-Chi Tung; Tzu-Pin Lu (BMC, 2021)
Abstract Background After implementing a nationwide harm reduction program in 2006, a dramatic decline in the incidence of human immunodeficiency virus (HIV) infection among people with injection drug use (IDU) was observed in Taiwan. The harm reduction program might have sent out the message discouraging the choice of IDU among illicit drug users in early stage. Based on the yearly first-time offense rates from 2001 to 2017, this study aimed to examine (1) whether the nationwide implementation of the harm reduction program in 2006 led to changes in first-time offenders' use of heroin; (2) whether the intervention had a similar effect on the use of other illicit drugs; and (3) whether the effect of the intervention was limited to the first-time offenders of young age groups. Methods Yearly first-time illicit-drug offense rates from 2001 to 2017 in Taiwan were derived from two national databases for drug arrests that were verified using urine tests: the Criminal Record Processing System on Schedule I/II Drugs and the Administrative Penalty System for Schedule III/IV Substances. A hierarchy of mutually exclusive categories of drug uses was defined by the drug with the highest schedule level among those tested positive in an arrest. Segmented regression analyses of interrupted time series were used to test for the impact of the 2006 intervention. Results There was a decrease of 22.37 per 100,000 in the rate for heroin but no detectable level changes in that for methamphetamine or ecstasy after the 2006 intervention in Taiwan. There were baseline decreasing trends in the first-time offense rate from 2001 to 2017 for heroin and ecstasy and an increasing trend for methamphetamine, with the slopes not altered by the 2006 intervention. The postintervention decrease in the first-time offense rate for heroin was detectable among offenders less than 40 years old. Conclusions Our results indicate a diffusion effect of the 2006 intervention on decreasing heroin use among young offenders and have policy implications for better prevention and treatment for different age groups.